PENCIPTAAN BUKU KOMIK SEBAGAI UPAYA PENGENALAN PERMAINAN TRADISIONAL KEPADA REMAJA - Pinasti, Rohry Dinda; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: The purpose of this study was to the creation of comic books of traditional games as an attempt to introduce to teenagers. Traditional games currently almost eroded and replaced with electronic games, with all modern tools as well. This is mainly due to the rapid development of technology that supports and produces various types of games, so there is little youth of today are not familiar with the traditional games ever played by their parents. Whereas the traditional game is part of a culture that must be preserved and introduced because it has a lot of values and positive benefits for the development of intellectual, social, emotional, and personality teenagers.Â Keywords: Comics, Design, Traditional Games,Teenagers